Rasm Al-Qur'an: Pilar Keotentikan Kitab Suci dan Penguat Nilai-Nilai Moderasi Islam - Stiyana, Wiwit; Masian; Hasbullah; Nursaktila, Nia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the Rasm al-Qur'an system as a method of Qur'anic writing that not only functions to preserve the authenticity of the revealed text but also embodies and reinforces the values of religious moderation in Islam. Using a qualitative-descriptive approach with library research method, this study analyzes primary sources such as classical 'ulum al-Qur'an books (al-Qurṭubi, al-Ālūsī, al-Dānī) as well as contemporary works on Islamic moderation, supplemented by secondary sources including indexed scientific journals. The findings indicate that Rasm al-Qur'an, standardized during the era of Caliph Uthman bin Affan, serves as an epistemological pillar preserving the purity of revelation through principles of meticulousness, rigorous verification, and an unbroken chain of scholarly transmission tracing back to Prophet Muhammad SAW. This system reflects the values of wasaṭiyyah (moderation) such as balance (tawāzun), justice ('adl), proportionality (i'tidāl), and tolerance (tasāmuh). The diversity within Rasm schools (Al-Dānī and Abū Dāwūd) as well as differences in application across modern mushafs (Madinah Mushaf and Indonesian Standard Mushaf) actually demonstrate the spirit of moderation—not dividing the ummah, but rather enriching Islamic scholarly heritage. This study concludes that deep understanding of Rasm al-Qur'an can serve as a natural filter against exegetical extremism while simultaneously providing a methodological foundation for strengthening authentic religious moderation in the contemporary era